3D Mafic Topography of the Transition Zone between the North-Western Boundary of the Congo Craton and the Kribi-Campo Sedimentary Basin from Gravity Inversion - Sévérin Nguiya; Willy Lemotio; Philippe Njandjock Nouck; Marcelin M. Pemi; Alain-Pierre K. Tokam; Evariste Ngatchou (International Journal of Geophysics)
The structure of the transition zone between the north-western boundary of the Congo Craton and the Kribi-Campo sedimentary basin is still a matter of scientific debate. In this study, the existing gravity data are interpreted in order to better understand the geodynamics of the area. Qualitatively, results show that the major gravity highs are associated with long-wavelength shallow sources of the coastal sedimentary basin, while large negative anomalies trending E-W correlate to low dense intrusive bodies found along the northern limit of the Congo Craton. For the delineation of the causative sources, the gravity anomalies have been inverted based on the Parker-Oldenburg iterative process. As inputs, we used a reference depth of 20 km obtained by spectral analysis and successively, the density contrasts 0.19 g/cm3 and 0.24 g/cm3, deduced from available 1D shear wave velocity models. The results reveal an irregular topography of the mafic interface characterized by a sequence of horst and graben structures with mafic depths varying between 15.6 km and 23.4 km. The shallower depths (15.6-17 km) are associated with the uprising of the mafic interface towards the upper crust. This intrusion may have been initiated during the extension of the Archean Ntem crust resulting in a thinning of the continental crust beneath the coastal sedimentary basin. The subsidence of the mafic interface beneath the craton is materialized by 2 similar graben structures located beneath both Matomb and Ebolowa at a maximum depth of 23.4 km. The intermediate depths (18-22 km) are correlated to the suture zone along the Pouma-Bipindi area. The location of some landslides across the area matches within the northern margin of the Congo Craton and suggests that this margin may also impact on their occurrence. This work provides new insights into the geodynamics, regional tectonics, and basin geometry.